Manfaat madu bagi kesehatan menurut al-qur'an: Manfaat madu bagi kesehatan menurut al-qur'an - Nur Ilmi Hayati (LPPM STIKes Muhammadiyah Ciamis, 2022)
Improving the immune system and reducing the risk of respiratory infection is vital during the deployment of the covid virus 19. Hence, we need to consume natural products like honey. The qur 'an of honey contains many medicinal properties for various diseases.